MAKNA EPITAP KUBURAN KI AGENG KEBOKENONGO DI SITUS PENGGING DALAM MANFAAT ILMU PEMERINTAHAN - Abdul Choliq Nawawi (Berkala Arkeologi, 1998)
The epitaph at the Pengging Site is engraved on a teak wood board, located above the doorway of Ki Ageng Kebokenongo's grave cupola in Gedong, Dukuh village, Banyudono district. This epitaph is in Arabic and is script in the Tsuluts style consists of only one line. The letters were still in good condition, except for a word which was slightly damaged. On the right and the left side of this epitaph are found two symbols of the sun, each of which shines eight rays and is often referred to as the rays of "Surya Majapahit". The type of year number used in this epitap is the Arabic alphabet. The information contained in this epitaph mentions the existence of government institutions such as: guardians, scholars and shaykhs akbar.